2021
DOI: 10.3390/ijerph18136942
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Fine Particulate Matter (PM2.5) Concentrations from Burning Solid Fuels in Rural Households of Butajira, Ethiopia

Abstract: The use of solid fuel, known to emit pollutants which cause damage to human health, is the primary energy option in Ethiopia. Thus, the aim of this study was to measure the level of household air pollution by using the 24-h mean concentration of fine particulate matter (PM2.5) in 150 randomly recruited households in rural Butajira, Ethiopia. Data relating to household and cooking practices were obtained by conducting face-to-face interviews with the mothers. The 24-h mean (standard deviation) and median PM2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Compared to other pollutants, particulate matters (PM) were studied the most where thirty-eight mean concentration values were analyzed for PM 2.5 ( Adane et al., 2021 ; Admasie, 2019 ; Downward et al., 2018 ; Edlund, 2019 ; Embiale et al., 2020a , 2021 ; Graham, 2011 ; Okello et al., 2018 ; Pennise et al., 2009 ; Sanbata et al., 2014a ; Tamire et al., 2021 ; Zwaag, 2016 ), PM 4 ( Keil et al., 2010 ), PM 10 ( Embiale et al., 2019 , 2020b , 2021 ), and TSP ( Embiale et al., 2019 , 2020a , 2021 ; Keil et al., 2010 ; Tadesse, 2015 ). The calculated mean average concentration for PM 2.5 was 477.47 μg/m 3 in the households of Ethiopia as shown in Figure 3 and Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to other pollutants, particulate matters (PM) were studied the most where thirty-eight mean concentration values were analyzed for PM 2.5 ( Adane et al., 2021 ; Admasie, 2019 ; Downward et al., 2018 ; Edlund, 2019 ; Embiale et al., 2020a , 2021 ; Graham, 2011 ; Okello et al., 2018 ; Pennise et al., 2009 ; Sanbata et al., 2014a ; Tamire et al., 2021 ; Zwaag, 2016 ), PM 4 ( Keil et al., 2010 ), PM 10 ( Embiale et al., 2019 , 2020b , 2021 ), and TSP ( Embiale et al., 2019 , 2020a , 2021 ; Keil et al., 2010 ; Tadesse, 2015 ). The calculated mean average concentration for PM 2.5 was 477.47 μg/m 3 in the households of Ethiopia as shown in Figure 3 and Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…This was due to the highest emissions from indoor biomass fuel use, domestic activities such as coffee ceremony, baking injera , wot preparation, poor ventilation, and housing conditions. According to Tamire et al. (2021) , households using only traditional stoves and those that did not open the door or window during cooking had a significantly higher mean concentration compared with their counterparts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 150 households in rural Ethiopia, Tamire et al 28 found that the average duration of cooking per 24 hours was 258 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Titcombe et al 27 measured indoor PM 2.5 in a pilot study in homes in Tanzania and found average exposures during cooking events of 1574 ± 287 μg/m 3 when using firewood and 588 ± 347 μg/m 3 when using charcoal, which is in the same range as in our laboratory experiments. In a study of 150 households in rural Ethiopia, Tamire et al 28 found that the average duration of cooking per 24 hours was 258 minutes. Assuming that cooking (including coffee making) is conducted for a total average of 4 hours per day, the 24‐hour average exposure due to cooking alone would be 53 μg/m 3 using charcoal (average of the two types in this study), 1300 μg/m 3 using wood (average of the two types in this study), 35 μg/m 3 using crops residue(a remarkably low value in this context which motivates further experiments for verification), and 2700 μg/m 3 using dung.…”
Section: Discussionmentioning
confidence: 99%